Improvement of BIPV Efficiency by Application of Highly Reflective Surfaces at the Building Envelope - Dominika Knera (MDPI AG, 2021)
The use of concentrated solar irradiation for the improvement of electric generation improvement has been implemented on different scales, mainly in photovoltaic systems. High-concentration Fresnel lenses are widely chosen for this approach in large installations, while low-concentration systems are rather applied in medium-low scales. For the latter, the improvement on electric performance was revealed, even when no solar tracking was implemented. The presented work aims to analyse a low-concentration photovoltaic installation by a numerical approach. First, the reflective surfaces were designed geometrically considering the optimal slope determined for each month. Subsequently, different simulation techniques were used separately for prediction of solar irradiation and energy production. Three criteria were selected to analyze power generation: the highest increase in total annual solar irradiance on panels with reflective surfaces, the highest total annual solar irradiance collected, and the optimal slope of panels for the entire year. The increase in energy was found to not exceed 10% in the winter months. Whereas in the spring and summer months the energy improvement is about 15–20%. Moreover, it was observed that the temperature of the proposed concentration photovoltaic system increased significantly, reaching more than 90 °C, while for traditional PV panels it did not exceed 75 °C.